Masalah Vehicle Routing Problem pada Pengiriman Barang di Kota Bandung Utara dengan menggunakan Kluster K-Means dan Algoritma Nearest Neighbor - Debby Agustine; Ibnu Hadi Hadi; Devi Eka Wardani Meganingtyas (Program Studi Matematika Universitas Negeri Jakarta, 2022)
The Vehicle Routing Problem (VRP) is an optimization problem in determining the route of packet distribution with limited vehicle capacity. Routing in the distribution of packets is important so that the shortest route will be sought so that the package arrives on time. One of the algorithms that discusses the search for vehicle routes with VRP problems is the Nearest Neighbor Algorithm, as for the stages in finding the best route by enumerating all possible sequences of existing routes and selecting the best set of routes in order to find the shortest route from one node to all other nodes. so it becomes a connected route.